La relación entre control interno y eficiencia operativa en la empresa Bitel en Iquitos, año 2022 - Cisneros Panduro, Jhon Antony (2023)
This study explored the relationship between the implementation of the internal control system and operational efficiency at Bitel Iquitos in the year 2022. Using a quantitative approach with a sample size of 53 administrative workers, the Spearman correlation coefficient was applied, revealing a moderate and significant correlation (Rho of 0.691, p-value of 0.023) between internal controls and operational efficiency. The adoption of the COSO model also showed a positive correlation with customer satisfaction (Rho of 0.371, p-value of 0.039), and a moderate relationship was found between operational errors and operational cost (Rho of 0.512, p-value of 0.037). These results underscore the importance of robust internal control systems to optimize operations and improve customer experience, providing evidence for business management improvement strategies.